2019
DOI: 10.1259/bjr.20180986
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of an ADC-based radiomics model for predicting pelvic lymph node metastases in patients with stage IB–IIA cervical squamous cell carcinoma

Abstract: Objectives: To investigate the prediction value of a radiomics model based on apparent diffusion coefficient (ADC) maps for pelvic lymph node metastasis (PLNM) in patients with stage IB–IIA cervical squamous cell carcinoma (CSCC). Methods: A total of 153 stage IB–IIA CSCC patients who underwent preoperative MRI including DWI from January 2015 to October 2017 were retrospectively studied and divided into a training cohort ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 42 publications
1
29
2
Order By: Relevance
“…We defined the DL model-predicted LNM probability as the DL score. Owing to the inconsistency of previous research about the performance of MRI sequences, [13][14][15][16] we compared the DL model among 3 MRI sequences to find the optimal model for LNM prediction.…”
Section: Model Development and Visualizationmentioning
confidence: 99%
See 2 more Smart Citations
“…We defined the DL model-predicted LNM probability as the DL score. Owing to the inconsistency of previous research about the performance of MRI sequences, [13][14][15][16] we compared the DL model among 3 MRI sequences to find the optimal model for LNM prediction.…”
Section: Model Development and Visualizationmentioning
confidence: 99%
“…The median survival time for DFS was 31 (IQR, 16-56) months in the primary cohort and 23 (IQR, [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] months in the validation cohort. Figure 2C, D shows a significant difference between low-and high-risk patients from the hybrid model in the primary cohort (hazard ratio, 3.24; 95% CI, 1.64-6.44; P < .001) and validation cohort (hazard ratio, 4.59; 95% CI, 2.04-10.31; P < .001).…”
Section: Prognostic Value Of the Hybrid Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy has shown a great potential for improved diagnostic and prognostic in a wide range of cancer types (16)(17)(18)(19). Few studies have suggested improvement in preoperative prediction of LNM by using different modalities-based radiomics analysis in cervical cancers (20)(21)(22)(23). However, these studies might suffer from relatively small sample sizes, analysis of single sequence or Abbreviations: LNM, lymph node metastasis; PLND, pelvic lymph node dissection; FIGO, International Federation of Gynecology and Obstetrics; MRI, magnetic resonance imaging; CSCC, cervical squamous cell cancer; DWI, diffusion-weighted imaging; FOV, field of view; ADC, apparent diffusion coefficient; ROI, region of interest; GLCM, gray-level co-occurrence matrix; GLRLM, gray-level run length matrix; GLSZM, gray-level size zone matrix; NGTDM, neighboring gray tone difference matrix; GLDM, gray-level dependence matrix; LoG, Laplacian of Gaussian; ICC, interclass correlation coefficient; MRMR, minimum redundancy maximum relevance; LASSO, least absolute shrinkage and selection operator; ROC, receiver operating characteristic; DCA, decision curve analysis.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy has shown a great potential for improved diagnostic and prognostic in a wide range of cancer types ( 16 19 ). Few studies have suggested improvement in preoperative prediction of LNM by using different modalities-based radiomics analysis in cervical cancers ( 20 23 ). However, these studies might suffer from relatively small sample sizes, analysis of single sequence or single section rather than whole-tumor volume analysis, or lack of external validation.…”
Section: Introductionmentioning
confidence: 99%